2012
DOI: 10.1155/2012/814913
|View full text |Cite
|
Sign up to set email alerts
|

Effect of S-PRG Eluate on Biofilm Formation and Enzyme Activity of Oral Bacteria

Abstract: Recently, the antibacterial activity of a composite resin containing prereacted glass ionomer (S-PRG) filler was revealed. We examined the effect of an S-PRG eluate on various biologic activities of Streptococcus mutans and Porphyromonas gingivalis. Adherence ability of S. mutans was evaluated by microtiter plate assay; protease and gelatinase activities of P. gingivalis were examined by synthetic substrate hydrolysis and gelatin film spot assay, respectively. Coaggregation of P. gingivalis with Fusobacterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 37 publications
0
41
3
2
Order By: Relevance
“…In accord with this last report, we observed that EVA containing S-PRG filler inhibited the growth of S. mutans and the formation of biofilms in an S-PRG filler content-dependent manner. Yoneda et al have reported that S-PRG filler suppresses the proteolytic activity of gingipains 25) , the enzymes classified as cysteine proteinases, playing a major role in the pathogenesis of periodontitis 35) . The gingipains have an important role in the growth of P. gingivalis 36) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accord with this last report, we observed that EVA containing S-PRG filler inhibited the growth of S. mutans and the formation of biofilms in an S-PRG filler content-dependent manner. Yoneda et al have reported that S-PRG filler suppresses the proteolytic activity of gingipains 25) , the enzymes classified as cysteine proteinases, playing a major role in the pathogenesis of periodontitis 35) . The gingipains have an important role in the growth of P. gingivalis 36) .…”
Section: Discussionmentioning
confidence: 99%
“…These multiple ions eluted from some S-PRG filler-containing dental materials have various bioactive effects, such as strengthening of the tooth structure [16][17][18] , anti-plaque effect 19,20) , dentin remineralization [21][22][23] , acid-buffering capacity 15,24) , and inhibition of enzymatic activity of periodontopathic bacteria 25,26) . However, no studies have addressed the bioactive effect of mouthguards containing the S-PRG filler.…”
Section: Introductionmentioning
confidence: 99%
“…S-PRG suppressed the protease and gelatinase activities of P. gingivalis [38], which is associated with the progression of periodontal disease. Some materials that inhibit the protease activity of P. gingivalis have been developed, but most of them are in liquid form, while S-PRG shows antibacterial activity as both a solid form material or its eluate.…”
Section: Effect On Enzyme Activities Of Porphyromonas Gingivalismentioning
confidence: 96%
“…In addition, S-PRG fillers release several types of ions (e.g., fluoride, boron, silicate, aluminum, sodium, and strontium) 4) . The release of such ions prevents bacterial adhesion 5) , suppresses biofilm formation 6,7) , prevents demineralization 8,9) , and enhances remineralization 10,11) . Like calcium (Ca), strontium (Sr) is an alkaline earth element and has similar physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%